The transition from feature to object: Storage unit in visual working memory depends on task difficulty. - Qian, Jiehui; Zhang, Ke; Liu, Shengxi; Lei, Quan (Memory & Cognition, 2019)
Visual working memory (VWM) is a cognitive memory buffer for temporarily processing and storing visual information. Previous studies suggest that its capacity is severely limited, and there is an ongoing debate on whether the storage capacity is object-based or feature-based in VWM. In this study, a change-detection task was employed to investigate whether and how task difficulty can affect VWM, specifically, its capacity and the unit of storage. Task difficulty was manipulated through the set size of memory items, memory fidelity required by the resolution of representation and the type of feature tested. We examined two types of stimuli: the single-feature type, where each memory item was composed of a single feature (color or shape), and the conjunctive-feature type, where each item was composed of a conjunction of two features (colored shape). Experiment 1 replicated the previous findings that memory capacity for colors was larger than shapes, and decreased with the resolution demand regardless of the type of stimuli. In Experiment 2, we analyzed and compared the results from single-feature items and conjunctive-feature items in the low- and high-resolution conditions while controlling for the number of to-be-remembered features. By directly matching the estimated capacity based on an object-unit and a feature-unit with the theoretical prediction, the results showed that the unit storage in VWM tended to be feature-based with low task difficulty, and to be object-based with high task difficulty. This suggests that VWM is dynamic and flexible, dependent on the load of the current task.